Evaluación de la influencia de actividades productivas del cultivo yuca, en la calidad del suelo, comunidad San Pablo de Tarugo - Zambrano Acosta, Jaime Alfredo (2016)
The research aimed to evaluate the influence of the production activities of yucca cultivation in soil quality of San Pablo de Tarugo community. It was a non-experimental research, descriptive and quantitative chemical analysis laboratory test on the samples taken preharvest and harvest time in three batches of selected yucca production methods were used. The results showed to be relevant for the production process of yucca to the activities of soil preparation, preparation of cuttings, planting, replanting, weeding, harvesting, packaging and marketing as usual in the area of cultivation activities. Chemical analyzes of soil indicates that values of P, K, Ca, Mg is at its highest level, while the OM (organic matter) is located between the middle and lower level, its pH varies between ranges slightly acid, according to the values established by the Laboratory of soil, plant tissues and waters Pichilingue Experiment Station -INIAP. Considering these results as a guide to good environmental practices that has activities and policies to improve crop yields and protect the ecosystem.